2012
DOI: 10.1038/emboj.2012.89
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for Arf6-MKLP1 complex formation on the Flemming body responsible for cytokinesis

Abstract: A small GTPase, Arf6, is involved in cytokinesis by localizing to the Flemming body (the midbody). However, it remains unknown how Arf6 contributes to cytokinesis. Here, we demonstrate that Arf6 directly interacts with mitotic kinesin-like protein 1 (MKLP1), a Flemming body-localizing protein essential for cytokinesis. The crystal structure of the Arf6-MKLP1 complex reveals that MKLP1 forms a homodimer flanked by two Arf6 molecules, forming a 2:2 heterotetramer containing an extended b-sheet composed of 22 b-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 63 publications
5
63
0
Order By: Relevance
“…Indeed, quantification of remnants in fixed cells using the ring marker MKLP1 (also known as KIF23) (Ettinger et al, 2011;Gromley et al, 2005;Joseph et al, 2012;Makyio et al, 2012;Steigemann et al, 2009) revealed that remnants are not removed even after extensively rinsing the cells (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, quantification of remnants in fixed cells using the ring marker MKLP1 (also known as KIF23) (Ettinger et al, 2011;Gromley et al, 2005;Joseph et al, 2012;Makyio et al, 2012;Steigemann et al, 2009) revealed that remnants are not removed even after extensively rinsing the cells (Fig. 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Arf6 localizes to the midbody during the late stages of abscission, through interaction with mitosis kinesin-like protein 1 (MKLP1). The Arf6-MKLP1 complex links the plasma membrane to the microtubules running through the midbody, a step required for cell separation (Makyio et al, 2012). These functions of Arf6 are probably not essential to cytokinesis in all cells, as Arf6-knockout mice are viable at birth (Suzuki et al, 2006) and a Drosophila Arf6 2/2 mutant has cytokinesis defects only in spermatocytes (Dyer et al, 2007).…”
Section: Arf Function In Mitosismentioning
confidence: 99%
“…The expression vector for C-terminally EGFP-tagged SCAP was constructed by subcloning a cDNA fragment containing the entire coding sequence of human SCAP into pEGFP-N1. The expression vector for Nterminally mRFP-tagged SREBP1c was constructed by subcloning a cDNA fragment containing the entire coding sequence of human SREBP1c into the pcDNA3-Kozac-mRFP-C vector (Makyio et al, 2012). The R503A mutation of SREBP1c was introduced into the SREBP1c cDNA using the QuikChange Lightning Site-Directed Mutagenesis Kit (Agilent Technologies).…”
Section: Recombinant Plasmids and Virusesmentioning
confidence: 99%